Challenges faced by trainee teachers during teaching practicum - Che Haron, Sueraya; Senik @ Kamaruddin, Zuraidah; Mustapha, Ariyanti; Salim al Rawahi, Mohammed Mabrook (RSIS, 2025)
Teaching practicum is a crucial component of teacher education, providing trainee teachers with real-world classroom experience. However, the transition from theory to practice presents numerous challenges that impact their professional development. This paper explores the difficulties faced by trainee teachers during their teaching practicum, including lesson planning, classroom management, adapting to school culture, and handling student behavior. Additionally, issues such as workload, limited support from mentors and supervisors, and difficulties in applying pedagogical theories in real classrooms are discussed. The findings highlight the need for more structured support systems, enhanced mentor-trainee collaboration, and practical exposure before practicum to better equip future educators. Addressing these challenges effectively can contribute to a more impactful teacher training program, ultimately improving the quality of education and teacher preparedness.